OCEANS 2000 MTS/IEEE Conference and Exhibition. Conference Proceedings (Cat. No.00CH37158)
DOI: 10.1109/oceans.2000.881822
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional reconstruction of the oscillatory free-surfaces of a flow over antidunes: stereoscopic and velocimetric techniques

Abstract: We present imaging methods developed to characterize the oscillatory free-surface of rapid flows and apply them to torrential currents propagating over sediment antidunes. The aim is to obtain high-resolution relief maps of the free-surface topography, in order to highlight the regular spatial patterns associated with the bedforms. Two measurement principles are outlined and tested, both based on the imaging of floating tracers dispersed on the rapidly flowing surface. The first relies on direct stereoscopic m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
1
1
0
Order By: Relevance
“…To permit cross-validation, the two methods are applied to the same experiments, while each relies on its own separate camera footage and data analysis pipeline. Preliminary results of the present research effort were reported in Devriendt et al (1998) and Douxchamps et al (2000).…”
Section: Introductionsupporting
confidence: 63%
“…To permit cross-validation, the two methods are applied to the same experiments, while each relies on its own separate camera footage and data analysis pipeline. Preliminary results of the present research effort were reported in Devriendt et al (1998) and Douxchamps et al (2000).…”
Section: Introductionsupporting
confidence: 63%
“…The second case is a mature debris flow of PVC particles featuring steep concentration and velocity gradients, and constitutes a challenging test for the particle-tracking techniques. Monocular imaging results for similar flows were presented in Capart et al (2002), while some preliminary stereo results were described in Douxchamps et al (2000) and Spinewine et al (2000).…”
Section: Introductionmentioning
confidence: 84%